2012: To be inside someone else’s dream: music for sleeping and waking minds - Ouzounian, G; Knapp, RB; Lyon, E; DuBois, RL (Springer, 2017)
Music for Sleeping and Waking Minds (2011–2012) is a new, overnight work in which four performers fall asleep while wearing custom designed EEG sensors which monitor their brainwave activity. The data gathered from the EEG sensors is applied in real time to different audio and image signal processing functions, resulting in continuously evolving multi-channel sound environment and visual projection. This material serves as an audiovisual description of the individual and collective neurophysiological state of the ensemble. Audiences are invited to experience the work in different states of attention: while alert and asleep, resting and awakening.